YOUTUBE AS A DA'WAH MEDIA - Ahmad Tamrin Sikumbang; Rahmi Fiutra Ulwani (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
The development of technology is currently experiencing rapid progress, a variety of media provide information without limit and time. Progress from various media in the information age has experienced significant changes in terms of actors, methods and effects. The presence of the internet and information products has succeeded in breaking through geographical barriers, national, racial, cultural and cultural boundaries. Citizens' activities are now increasingly important, considering that everyone can be directly connected through a global information network. The development in technology has a big influence on social life, especially in Indonesia, which easily access information offered by social media. The positive side of the presence of technology is that we can get various information about developments in various sectors both religion, education, economy, social culture and politics. While the negative elements are impressions that are not educational, full of violence and irrational. In various popular media, the presence of YouTube has become one of the easy tools in spreading da'wah, where people no longer have difficulty watching and listening to religious studies that are not always shown on the media such as on television. Da'wah through YouTube media has included various groups of people both parents, teenagers and children, in addition to making it easy for the preachers (preachers) to spread the teachings of Islam through YouTube also makes it easy for the public to access various lectures that he wants to listen to a variety of different topics and speakers.Keywords: youtube, media, dakwah